2018
DOI: 10.1590/0103-6440201801553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 35% Hydrogen Peroxide on Color and Translucency Changes in Enamel and Dentin

Abstract: This study evaluated the effects of tooth bleaching with high-concentration of hydrogen peroxide on alterations of translucency parameter (TP) and color of dentin and enamel. The crown of five human molars was sectioned into four slices parallel to buccal surface. The dentin of external slices containing buccal/ lingual enamel was fully removed with diamond bur; while these slices were used to assess alterations on enamel. Alterations on dentin were assessed into the center of internal slices. The color of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…This diffusion phenomenon was first described by Haywood 6 in 1990 and consists in the ability of peroxide to diffuse through the tooth structure, 2,7-9 generate free radicals and degrade organic molecules responsible for intrinsic or extrinsic staining of dental structure. 1,2,7,[9][10][11] Color change in teeth with orthodontic bracket has been proven by some studies and this undesirable result might be caused by the permanent iatrogenic enamel effects associated with bonding, debonding, and cleaning procedures, [12][13] enamel demineralization, 14 exogenous and endogenous discoloration of the tooth and remaining adhesive material 12,15 and the color instability of the resin used to retain the bracket. 16 Among the doubts of the orthodontic patient is wondering when is the best time to perform the whitening procedure, as in addition to well-aligned teeth, they idealize white teeth and want the procedure as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…This diffusion phenomenon was first described by Haywood 6 in 1990 and consists in the ability of peroxide to diffuse through the tooth structure, 2,7-9 generate free radicals and degrade organic molecules responsible for intrinsic or extrinsic staining of dental structure. 1,2,7,[9][10][11] Color change in teeth with orthodontic bracket has been proven by some studies and this undesirable result might be caused by the permanent iatrogenic enamel effects associated with bonding, debonding, and cleaning procedures, [12][13] enamel demineralization, 14 exogenous and endogenous discoloration of the tooth and remaining adhesive material 12,15 and the color instability of the resin used to retain the bracket. 16 Among the doubts of the orthodontic patient is wondering when is the best time to perform the whitening procedure, as in addition to well-aligned teeth, they idealize white teeth and want the procedure as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Menezes et al [25] evaluated the impact of tooth whitening using 35% hydrogen peroxide in relation to the color and translucency of dentin and enamel. For the study, five healthy human molars were selected, and their crowns were sectioned into four slices parallel to the buccal surface.…”
Section: Structural and Chemical Characteristics Of Dental Tissues After Bleachingmentioning
confidence: 99%
“…In fact, the contribution of each tissue to the overall color change caused by tooth bleaching remains controversial. [13][14][15][16] Moreover, to the best of our knowledge, no prior study has assessed the effect of a metallic bracket on the individual color changes in enamel and dentin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that color changes in both dentin and enamel contribute to the bleaching effect, 10‐12 but information about the possible effect of brackets on the individual color changes of each tooth tissue is lacking. In fact, the contribution of each tissue to the overall color change caused by tooth bleaching remains controversial 13‐16 . Moreover, to the best of our knowledge, no prior study has assessed the effect of a metallic bracket on the individual color changes in enamel and dentin.…”
Section: Introductionmentioning
confidence: 99%